Transformation of Economic Education (Bibliometric Analysis) - Kurniadi, Romi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study aims to identify trends in economic education research as a reaction to the dynamics of changing economic phenomena, which are key topics for economic education discussions. Economic education must change to address concerns with the changing demands for economic education in terms of graduate competencies, employment prospects, and community needs. Trend analysis is conducted by bibliometric analysis to meet this objective. The technique used is bibliometric analysis, which involves four stages: establishing the goal and scope of the study, choosing the appropriate bibliometric analysis tools, gathering data for analysis, and finally conducting the analysis and summarizing the results. The data source comes from the Google Scholar database which is collected through the Publish or Perish application using a combination of the keywords economic education, entrepreneur education, and job prospects. Data are in the form of articles published in journals and proceedings for 2017-2022. A total of 1,458 data were selected to become 1,390 data for analysis. The analysis technique used is a performance analysis and network analysis using the VOS Viewer application. The results of the performance analysis show that many studies on economics education have been published in reputable international journals and have received high citations.